Expanding Single Brackets 1

Easy

Medium

Difficult

Q1) 3(z + 2) =
Q1) 10y(2y + 7) =
Q1) 6(5y + 9) +8y + 9 =
Q2) 9(x + 10) =
Q2) 10z(2z + 7) =
Q2) 5(8y -2) +7y + 5 =
Q3) 4(w + 2) =
Q3) 2x(5x -2) =
Q3) 4(4y + 8) +9y -2 =
Q4) 2(z + 4) =
Q4) 9y(4y -2) =
Q4) 6(10y -7) +10y + 3 =
Q5) 9(w + 7) =
Q5) 9y(8y + 2) =
Q5) 3(3y + 3) -4y + 8 =
Q6) 9(w + 4) =
Q6) 10y(6y -2) =
Q6) 8(6z -5) -7z -10 =
Q7) 7(w + 7) =
Q7) 10z(5z + 2) =
Q7) 4(3y -10) -4y -4 =
Q8) 4(y + 5) =
Q8) 5x(3x + 3) =
Q8) 10(6y -5) +6y -4 =
Q9) 4(x + 3) =
Q9) 7z(3z + 4) =
Q9) 7(10w + 3) +8w + 2 =
Q10) 9(x + 7) =
Q10) 4y(6y -6) =
Q10) 5(2z + 10) +5z -9 =